Application of information technologies in the organization of the educational process - Kolpakova T. O. (Digitalization in the education system: best practices and implementation practices, 2025)
The work is devoted to the practical experience of using information technologies in the organization of the educational process in the system of secondary professional medical education. The practice of using electronic platforms is being considered.
Keywords: информационные технологии; среднее профессиональное образование; information technology; медицинское образование; онлайн-курс; организация образовательного процесса; medical education; online course; secondary vocational education; organization of the educational process